2021
DOI: 10.3390/plants10020252
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antifungal Activity of the Extracts of Different Parts of Avicennia marina (Forssk.) Vierh

Abstract: Increased problems associated with side effects and bacterial resistance of chemical drugs has prompted the research focus on herbal medicines in the past few decades. In the present investigation, the antimicrobial activity of the various parts of Avicennia marina (AM), a mangrove plant, has been evaluated. The plants were collected from the Jazan area of the Kingdom of Saudi Arabia. Primary extracts of roots, stem, leaves, fruits, and seeds were made in ethanol and fractioned in ethanol, ethyl acetate, petro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 42 publications
0
32
0
1
Order By: Relevance
“…The petroleum ether extract from flowers of Hibiscus rosa-sinensis at concentrations of 4 mg/disc and 2 mg/disc displayed the strongest inhibition zones of Staphylococcus aureus [ 47 ]. Avicennia marina extracts of the roots, fruits, and seeds showed the highest antifungal activity against Aspergillus fumigatus and Candida albicans [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…The petroleum ether extract from flowers of Hibiscus rosa-sinensis at concentrations of 4 mg/disc and 2 mg/disc displayed the strongest inhibition zones of Staphylococcus aureus [ 47 ]. Avicennia marina extracts of the roots, fruits, and seeds showed the highest antifungal activity against Aspergillus fumigatus and Candida albicans [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many scientific reports have shown potential foliar extracts of mangrove against microbial pathogens and suggested considering the mangrove plants as a valuable source for the bioactive chemicals of immense medicinal values. 32 One type of mangrove that is widely spread in various locations in Indonesia such as in Teluk Awur, Central Java is A. corniculatum. Mangrove has the potential as an antimicrobial against the causative agent of vibriosis.…”
Section: Discussionmentioning
confidence: 99%
“…These plants are a repository of phytochemicals in the form of secondary metabolites, such as steroids, phenols, tannins, terpenoids, alkaloids, and flavonoids, which have established antimicrobial properties and could be developed for treatment of infectious diseases [17]. Innumerable studies worldwide have reported the antimicrobial potency of medicinal plants with a handful focussed on expounding the antimicrobial potency of isolated compounds [18,8,19,20,21,22,23].…”
Section: Discussionmentioning
confidence: 99%